Design, development and recent experiments of the CIMPLE-PSI device. (5th June 2019) - Kakati, Mayur; Sarmah, Trinayan; Aomoa, Ngangom; Sabavath, Gopikishan; Dihingia, Pubali; Rahman, Mizanur; Ghosh, J.; Saxena, Y.C.; Satpati, B.; Sharma, Gagan; Gupta, Ajay; De Temmerman, G.
Abstract: The CIMPLE-PSI laboratory in India's northeast corner has been engaged over the last decade in the development of advanced experimental systems for controlled plasma fusion-relevant plasma surface interaction (PSI) studies and material testing. The CIMPLE-PSI experimental device was commissioned recently, where a magnetized collimated helium plasma beam is produced under steady-state conditions inside a linear vacuum chamber, which can be made to interact with remotely placed material targets, under controlled experimental conditions. This paper reports on the design, development of the major sub-systems of this device and the performance of the integrated system. The peak helium ion flux and heat flux were measured as 10 24 m −2 s −1 and 5.1 MW m −2, respectively; this confirms that extreme ITER divertor-like parameters are successfully reproduced by this simulation device. Steady-state operation of the electromagnet allowed prolonged operation of the plasma leading to a very high fluence of 0.3 × 10 28 m −2, which may be enhanced further in the future. Tungsten samples were exposed in this device under helium plasma that had led to the formation of nanometer-sized tungsten fibre foam structures on the target. The technique of grazing incidence small angle x-ray scattering was successfully utilized to measure the average size of the helium bubbles remaining buried in the exposed sample and its variation with depth from the top of the surface.